Evaluating Supply Chain Resilience Strategies in Passion Fruit Agro-Industrial Processing Using the SCOR 14.0 Racetrack Framework - Asrul Fole; Khoerun Nisa Safitri; Nurul 'Aini; Billi Syufrian; Riska Iva Riana (Agroindustrial Technology Journal, 2026)
Global agro-industrial supply chains face increasing risks of disruption due to climate variability, seasonal availability of raw materials, and weak coordination among stakeholders. The passion fruit processing industry in Makassar is a perishable agroindustry highly vulnerable to fluctuations in raw material supply, production interruptions, and delivery delays. This study aims to evaluate and improve supply chain resilience using the SCOR Digital Standard 14.0 Racetrack Framework, with an emphasis on the performance attributes of reliability, responsiveness, and agility. A quantitative descriptive case study approach was employed using direct observations, semi-structured interviews, and analysis of historical data on production, inventory, and distribution activities. Resilience performance was assessed using SCOR 14.0 Level 1–3 metrics and benchmarked against internal performance targets. Root causes of performance gaps were identified using Fishbone diagrams, while improvement initiatives were structured into project charters and prioritized through an impact–effort assessment. The results indicate substantial performance gaps before improvement. Reliability metrics Level 3 showed Customer Commit Date Achievement (RL3.3) at 80% and Orders Received Damage-Free (RL3.10) at 86%, both below targets. Responsiveness indicators, including Source Order Cycle Time (RS3.1) and Make Order Cycle Time (RS3.12), achieved only 75% and 78%, respectively. Agility exhibited the largest deficiencies, particularly in Upside Source Flexibility (AG3.2) and Upside Make Flexibility (AG3.9). Following the implementation of 18 prioritized improvement projects, all resilience metrics reached or closely approached target levels. These findings confirm that the SCOR 14.0 Racetrack Framework provides a systematic and effective approach for enhancing supply chain resilience in perishable agro-industries through structured operational and managerial interventions.